a - Muslem Hamdani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Recitation that is practiced by a Muslim continuously and uninterruptedly will be an innovative force in individuals who are facing heart disease, mental illness and mental disorders. Dhikr is an effective medium for achieving the goal of da'wah, therefore, coaching dhikr to the community is felt to be able to open hearts and minds to return to the way of Allah. The effectiveness of dhikr as a medium of da'wah can be seen from how this dhikr activity can achieve the goal of da'wah, namely, inviting people to carry out orders and stay away from His prohibitions. One of the habits of the members of a remembrance assembly is to focus and concentrate on the remembrance, so that the dhikr guide in carrying out the remembrance easily conveys the hasanah mauizah in the gaps of the remembrance, and the remembrance congregation also deeply absorbs the contents of the remembrance. Remembrance plays an important role in the educational process of Purification of the Soul (tazkiyyat al-nafs).